2022
DOI: 10.1093/infdis/jiac091
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Coronavirus-Specific Immunoglobulin G Responses to Complement Overactivation in Patients with Severe Coronavirus Disease 2019

Abstract: Background Excessive complement activation has been implicated in the pathogenesis of COVID-19, but the mechanisms leading to this response remain unclear. Methods We measured plasma levels of key complement markers, SARS-CoV-2 RNA and antibodies against SARS-CoV-2 and common cold coronaviruses (CCC) in hospitalized patients with COVID-19 of moderate (n=18) and critical severity (n=37), and healthy control subjects (n=10). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…The alternative complement pathway can also mediate complement amplification upon the triggering of the classical or lectin pathways. However, we did not find evidence of immune complexes (18,22) or direct lectin binding (17,24) leading to complement factor turnover, given the unaltered concentrations of C4a in circulation around the time of respiratory failure.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The alternative complement pathway can also mediate complement amplification upon the triggering of the classical or lectin pathways. However, we did not find evidence of immune complexes (18,22) or direct lectin binding (17,24) leading to complement factor turnover, given the unaltered concentrations of C4a in circulation around the time of respiratory failure.…”
Section: Discussioncontrasting
confidence: 75%
“…All three complement arms were shown to be activated in COVID-19 (17)(18)(19)(20)(21)(22)(23)(24); however, their relative contributions remain ill-defined. Whereas complement was initially described as a liver-derived cascade, studies have demonstrated unexpected celland tissue-specific production and functions for the complement system (8,(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Soluble C5b-9 levels were also increased and correlated with C5a, markers of inflammation and coagulation [ 12 , 33 , 36 , 68 , 70 , 71 , 78 , 120 , 125 , [129] , [130] , [131] , [132] , [133] , [134] ]. C5 was only elevated in three studies measuring C5 levels [ 66 , 135 , 136 ]. MBL levels in plasma were in general higher in COVID-19 patients compared with healthy controls [ 134 , 137 , 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soluble levels of C5b-9 were also increased and correlated with C5a, markers of inflammation and coagulation [ 12 , 33 , 36 , 68 , 70 , 71 , 78 , 120 , 125 , [129] , [130] , [131] , [132] , 134 ]. C5 was only elevated in three observational studies investigating C5 [ 66 , 135 , 136 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation